POEM: Practical ontology engineering model for semantic web ontologies. Issue 1 (31st December 2016) - Ali, Shaukat; Khusro, Shah
Abstract: Sundown of the twentieth century saw the emergence of the World Wide Web. A decade later, semantic web (SW) envisioned enriching of web-accessible information and services with machine-processable semantics to solve the problems of information management and sharing which are aroused by the success of the web. However, success of the SW largely depends on the availability of formal ontologies for representing and structuring information in different domains. To facilitate web ontology engineering (OE), methodologies are proposed by the researchers since years. However, OE particularly web OE is still immature and none of the methodologies is standardized for web OE projects as yet. This paper presents an evolutionary SW ontology engineering methodology called POEM. POEM presents a complete methodology comprising of various phases for performing conceptualization, designing, implementation, evaluation, and project management tasks. POEM exploits and incorporates the large experiences from the widely used software engineering standards to make the methodology more realistic and provide greater functionality. Due to its broad nature, POEM has the potential applicability in a wider range of OE projects. Comparison of POEM with other OE methodologies has ascertained POEM as more advantageous and easy methodology for SW ontology engineering.